ANALISIS PENGARUH VARIASI DEBIT AIR TERHADAP KECEPATAN PUTARAN TURBIN CROSSFLOW PADA PEMBANGKIT LISTRIK TENAGA MIKROHIDRO - Kartono, N. A.; Indra Partha, C. G.; Ariastina, W. G.; Giriantari, I. A. D.; Satya Kumara, I N.; Sukerayasa, I W. (Jurnal SPEKTRUM; Vol 10 No 2 (2023): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2023.v10.i02.p6, 2023)
The Yeh Dikis River in Tabanan Regency Bali has a natural environment which is considered suitable to be used as a tourism destination. The factor that supports the Yeh Dikis River to become a tourism object is the river's potential to generate electricity. In this paper, a particular turbine for micro-hydro power plant is designed. The Yeh Dikis River has a water discharge of 0.381 m3/s with a head value of 8.2 meters, with a potential output power of 18.15 kW. The value of the water discharge and the output power are used to determine the type of turbine used. The computation and simulation showed that the crossflow turbine is suitable for the power plant. The analysis showed that a water discharge of 0.381 m3/s with a penstock diameter of 0.44 meters produces a specific rotational speed of 186 rpm; while a water discharge of 0.381 m3/s with a penstock diameter of 0.55 meters produces a turbine specification rotation speed of 160 rpm. This indicated that the effective head value affects the determination of the penstock diameter and the water velocity. The smaller diameter of the penstock produces, the higher the velocity of the water flow in the pipe. A low effective head will result in a low specific rotational speed. It was found that the optimum turbine power output for a water discharge of 0.381 m3/s with a penstock diameter of 0.44 meters is 18.15 kW. The work of the crossflow turbine is validated using a turbine simulator to determine the rotational speed of the turbine for a particular torque.